External envelope impact on thermal environment of heritage buildings from the colonial period in hot arid area - Terea, Chaker; Guedouh, Marouane Samir; Noureddine , Zemmouri (Technium Social Sciences Journal, 2022)
The present research aims to study the effectiveness of the envelope components of colonial dwellings in maintaining a comfortable indoor thermal environment. In hot and dry areas, extreme outdoor air temperatures compel designers to provide a better indoor thermal condition which remains a rather delicate task to achieve such as in the case of the city of Biskra. The heritage buildings were constructed in the colonial period in the Biskra region; the colonial district buildings are built with local materials such as mud bricks and stones that have a large thermal mass; these materials are the main component of the walls of the outer exterior skin. Onsite measurement campaigns were carried out to record air temperatures inside the inhabited area for 24 hours. Thereafter, the collected data were compared with the outdoor air temperatures to assess the effect of the envelope impact on the temperature variation. The important results remain in the envelope’s crucial effect to achieve thermal comfort using local materials with a high thermal mass.